Virtual Reality-Based Rehabilitation as a Feasible and Engaging Tool for the Management of Chronic Poststroke Upper-Extremity Function Recovery: Randomized Controlled Trial - Alejandro Hernandez; Liudmila Bubyr; Philippe S Archambault; Johanne Higgins; Mindy F Levin; Dahlia Kairy (JMIR Publications, 2022)
BackgroundA growing number of stroke survivors are left with little to no rehabilitation services upon discharge from stroke rehabilitation, although arm deficits may persist or develop from disuse once rehabilitation services have ceased. Virtual reality (VR)-based rehabilitation, combined with new technologies such as telerehabilitation, including serious games using VR environments that encourage users to practice functional movements from home with minimal supervision, may have an important role to play in optimizing and maintaining upper extremity (UE) function. ObjectiveThe primary objective of this study is to determine the extent to which a 1-month intervention using a VR-based serious game is effective in improving UE function compared with an evidence-based home exercise program. A secondary objective is to assess the feasibility of implementing the intervention for chronic stroke rehabilitation in participants' homes. MethodsA total of 51 chronic stroke participants were randomized to treatment (n=26, 51%; Jintronix system) or standard care (n=25, 49%; standardized Graded Repetitive Arm Supplementary Program kit home program) groups. The participants were evaluated at baseline (before), immediately after the intervention (after), and at follow-up (4 weeks). The primary outcome measure was the Fugl-Meyer Assessment for UE (FMA-UE). Secondary outcome measures included the Stroke Impact Scale and an abridged version of the Motor Activity Log-14. Self-reported number of sessions was logged for the standard care group. ResultsNo statistically significant differences between groups were found across measures. Overall time effects were found for the FMA-UE (P=.045), specifically between preintervention and postintervention time points for both groups (P=.03). A total of 9 participants in the treatment group reached or surpassed the minimal clinically important difference in scores for the FMA-UE, with 7 (78%) of them having baseline low or moderate arm function, compared with 3 (33%) participants in the standard care group. Furthermore, 56% (9/16) of the participants in the treatment group who actively engaged with the system reached the minimal clinically important difference for the FMA-UE, compared with none for the 0% (0/10) less-active participants. ConclusionsThese findings suggest that UE training for chronic stroke survivors using virtual rehabilitation in their home may be as effective as a gold standard home exercise program and that those who used the system the most achieved the greatest improvement in UE function, indicating its relevance to being included as part of ongoing rehabilitation services. Trial RegistrationClinicalTrials.gov NCT02491203; https://clinicaltrials.gov/ct2/show/NCT02491203 International Registered Report Identifier (IRRID)RR2-10.1016/j.cct.2015.12.006